Subcycle Wannier-Stark Localization by Mid-Infrared Bias in Gallium Arsenide - Bühler Johannes; Schmidt Christian; Heinrich Alexander-Cornelius; Allerbeck Jonas; Podzimski Reinold; Berghoff Daniel; Meier Torsten; Schmidt Wolf Gero; Reichl Christian; Wegscheider Werner; Brida Daniele; Leitenstorfer Alfred (EPJ Web of Conferences, 2019)
The fundamental interband absorption in gallium arsenide shows a strong blue shift when biased by mid-infrared transients exceeding 10 MV/cm. This subcycle feature is induced by the localization of electronic wavefunctions from 3D to 2D.